A Supervisão de Estágio da Licenciatura no IB-USP: Ensino por Investigação e Pesquisa - Prestes, Maria Elice Brzezinski; Silva, Rosana Louro Ferreira; Scarpa, Daniela Lopes (Revista de Graduação USP, 2017)
The teacher formation in the Course of Biological Sciences of the Institute of Biosciences of USP has undergone constant improvement since the new curriculum was implemented in 2007, in response to the USP Teacher Training Program (2004). Among the main actions, it is worth highlighting the current disciplines related to the supervision of the 100h internship at the IB-USP internship camp schools. Two disciplines were created, “Supervised Internship in Biology Teaching” and “Internship with Research in Biology Teaching”. Such disciplines allow not only the effective realization of the total number of hours of internship in schools, but more especially the development and implementation of intervention practices based on inquiry teaching, as well as intervention practices accompanied by a research exercise in the area of scientific education.. The initiatives have resulted in a very satisfactory fulfillment of the students teaching-learning objectives